Approaching information-seeking habits and their contextual features - Savolainen, Reijo (Information Research an international electronic journal, 2024)
Introduction. In information seeking, habits manifest themselves in the ways in which people repeatedly and regularly prefer and access certain sources of information. The present study reviews how researchers in diverse field have approached such habits and characterised their contextual features. Method. Qualitative content analysis of a sample of seventy-three studies on the above topic. The research inductively identified three approaches to habits in information seeking and contextual factors affecting habitual information seeking. Results. Many of the investigations on information-seeking habits approach them in terms of the frequency of information source use. Second, such habits are characterised in terms of information-seeking patterns. Third, the information practice approach directs the main attention to habits as integral constituents of people´s customary ways to seek access to information sources as a part of their daily routines. Information-seeking habits are influenced by contextual factors such as the time and place of information seeking, familiarity with information sources, and easy access to information. Conclusion. Information-seeking habits offer familiar and often efficient ways to identify and access information sources. There is a need to explore further the nature of habitual information seeking by conducting longitudinal studies charting people´s ways and motives to prefer similar sources across situations.